The importance of the archives community associations in Algeria during the colonial period 1900-1962 - sid ali, ahmed messoud (The Algerian Historical Journal, 2026)
This survey discussed the importance of the civil associations, that emerged during the two world wars ,as well as the challenge of the Algerian Patriotism that has banked at the beginning of the twentieth century, introducing new mechanisms of struggling in a new form of team work that appeared at that time and took various forms, contributing to the framework of the Algerian society which helped to restore the social cohesiveness through integration to associations that allowed them to develop their political consciousness fight.But the colonial Administration standed against. The local police of the municipalities had reported it, about these associations which had new visions of struggling to get back the National sovereignty. This is all what we wanted to discuss through this survey of this archive.